EFEKTIVITAS WEBSITE DALAM PELAYANAN ELEKTRONIK PEMERINTAH KOTA DEPOK - Nida Handayani (Universitas Muhammadiyah Jakarta, 2017)
This study uses qualitative descriptive study which will explain and describe the conditions of management of the website by looking at the initial appearance of the website, website development, government interaction with the public on the we- bsite, transactions or services carried out by the government to the public, and the connection or integration between the City of Depok work unit below it such as the Department, Agency, and others. The results of the study explained that, early occurrence of Depok City Government website is quite good by displaying various kinds of actual informa- tion related to the mission, vision, and duties and functions of Depok City Government. The development in Depok City Government website managed by the Office of Communications and Information is quite significant by adding several features that can help the public service. On the interaction media provided in Depok City Government portal are quite considerable; eg via email, website, facebook, twitter, rss, Sp @ce, and others that are quite interactive. Furthermore, the transaction or service with the local administration is substansial such as online permit service, online tax payment, and checking the status of eKTP. Lastly, connection or integration between Depok City Government website with the unit below it is sufficient although there are some that cannot be accessed. Supporting factors are the manager of the Depok City Government website namely Documentation and Information Management Officer (PPID) is quite interactive and always update data and information. Inhibiting factors are not all people can access the Depok City Government website due education-related abilities, as well as the lack of socialization related to some services that can be accessed through the Depok City Government website.Keywords: website, e-Government